Ueda, Immigrant America - A Social History - Tamura, Eileen (Teaching History: A Journal of Methods, 1997)
Postwar Immigrant America, which is part of the Bedford Series in History and Culture, provides the reader with a global understanding of a vital aspect of American history, one that makes the United States unique among nations of the world. More than any other country, the United States has played a distinctive role as destination for the millions of emigrants who, for one reason or another, have sought new lives in a place far from home. From 1820 to 1930, the United States received 61 percent of the world's emigrants, not only more than any other nation, but also more than the total of all other nations.